Talaq Menurut Perspektif Hukum dan Sosial dalam Konteks Islam - Idris Siregar; Nur Tasya Hariany Sitorus; Tari Nur Fajri (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Talaq is the release of marital ties or the breakdown of marital relations. The Islamic perspective on talaq exists because of the basic instructions for its permissibility in the Koran and hadith, even the ulama agree that Talaq is permissible under certain conditions for a husband who wants to divorce his wife. Talaq is prescribed in Islam but must be done in a certain way and at a certain time, such as divorcing the wife when the wife is pure or when the wife has not been intimate with her before. When divorcing your wifi, you must use regulations that are in accordance with the Talaq criteria. We will write this article to talk about Talaq according to Legal and Social Perspectives in an Islamic context. The purpose of this article is to find out Talaq from a legal and social perspective in an Islamic context and to know the Talaq problem in depth.